Improving Pedestrian Environment and Traffic Sign System with the Participatory Design at Anuban Ranong School - Somluk Bunnarong; Prapatpong Upala (My University, 2017)
The objective of this study is to design and improve the pedestrian environment and traffic signs with the participatory design at Ranong Kindergarten School. The result of this study was brought to identify the promotion of pedestrian safety zone. In the participatory process, the four groups were started up for collaboration including teacher and student group, local community group, academics group, and private organization group. The important finding was the “Brave Walk Unit,” the volunteer students who are the driven mechanism to promote other students who live near the school to walk or ride the bicycle to school on their own.Keywords: Participatory Design; Pedestrian Environment; Traffic Signs System, School zoneISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Promotion (chess); Safety Warnings and Signage